Beliefs, stereotypes and prejudices of the elderly towards aging (European Journal of Health Research, 2020)
Discrimination against older adults by age, because a negative beliefs, attitudes and prejudices is frequent but little accepted and reported. The objective is knowing types and frequency of beliefs, stereotypes and prejudices towards the aging by older adults in the city of Torreón, Coahuila, Mexico and its association with personal, social, family and work aspects. The material and method are crosssectional study, 572 elderly adults randomly selected from the population. Prior informed consent, the Scale on Prejudice to Aging and Aging and the Questionnaire on Negative Stereotypes towards Aging were applied. It was analyzed in SPSS 20. The results are: in the affective field (feeling and prejudices), the most negative dimensions are to be politically correct, social isolation and self-esteem, The most negative items are being slow, old, sick, fatigued and boring. In the cognitive sphere 87.2% refer negative beliefs and stereotypes towards aging, and are associated with having family dysfunction, difficulties in their personal care and over 75 years. In older adults the frequency of beliefs, stereotypes and prejudices negative to old age is high and is associated with family and health factors.